What Do We Have to Lose? Offloading Through Moral Technologies: Moral Struggle and Progress - Frank, Lily Eva (Sci Eng Ethics, 2019)
Moral bioenhancement, nudge-designed environments, and ambient persuasive technologies may help people behave more consistently with their deeply held moral convictions. Alternatively, they may aid people in overcoming cognitive and affective limitations that prevent them from appreciating a situation’s moral dimensions. Or they may simply make it easier for them to make the morally right choice by helping them to overcome sources of weakness of will. This paper makes two assumptions. First, technologies to improve people’s moral capacities are realizable. Second, such technologies will actually help people get morality right and behave more consistently with whatever the ‘real’ right thing to do turns out to be. The paper then considers whether or not humanity loses anything valuable, particularly opportunities for moral progress, when being moral is made much easier by eliminating difficult moral deliberation and internal moral struggle. Ultimately, the worry that moral struggle has value as a catalyst for moral progress is rejected. Moral progress is understood here as the discovery and application of new values or sensitization to new sources of harm.